Environmental Performance of Existing Cities and Green Infrastructures—Two Case Studies Compared: Reggio Calabria and Enna, Italy - Celestina Fazia (Urban Science)
There is growing awareness that there is a link between climate change and human influence and that human activities contribute to the warming of the atmosphere. The research identifies two ways to prepare cities to meet the challenges: the first is to optimize the way the urban organism functions by containing CO2 emissions and consumption of nonrenewable resources by indicating strategies to regenerate the existing city according to an ecosystem approach; the second is to preserve the natural areas of the peri-urban area through graded forms of protection and enhancement by curbing the settlement thrusts of the existing city. The article illustrates two case studies for comparison (Reggio Calabria and Enna) chosen in the context of two Italian regions. Both have urban planning laws that provide for new urban planning instruments sensitive to these aspects. The two case studies were selected because of the similarity of their physical characteristics and the types of agricultural production affecting large areas of land, which has been partially compressed over the years. The respective regional regulations provide solutions to increase protection while allowing for better sustainable use and enhancement.